Multiple-Choice Tests, Controlled and Free Writing: Can They Be Used to Measure Our Students’ Progress? - Martínez-Arbelaiz, Asunción (2012)
Los profesionales de la enseñanza de lenguas extranjeras o segundas lenguas se preguntan si sus alumnos progresan en el continuum del dominio de la lengua en cuestión. Sin embargo, dar evidencia «objetiva» del progreso de los aprendices nunca es tarea fácil. En USAC, un consorcio de universidades de Estados Unidos que ofrece cursos de español en países de habla hispana, se han adoptado diferentes formas de evaluación (assessment), como el test de opción múltiple, las redacciones dirigidas y las redacciones libres para diagnosticar el desarrollo lingüístico de los alumnos; todo ello tiene un impacto directo en el diseño de nuestros cursos. Professionals in the teaching of foreign or second languages often wonder whether their students are making progress in the language proficiency continuum. However, providing “objective” evidence of learners’ development is never an easy task. In USAC, a consortium of universities in the United States which offers courses of Spanish in Spanish-speaking countries, we have adopted several assessment measures, such as multiple-choice tests, and free and directed writing. This evidence is very valuable in order to diagnose learners’ linguistic development; and it has a direct impact on the design of our courses.